Genomic parallelism and lack thereof in contrasting systems of three‐spined sticklebacks. Issue 23 (27th July 2018) - Liu, Shenglin; Ferchaud, Anne‐Laure; Grønkjær, Peter; Nygaard, Rasmus; Hansen, Michael M.
Abstract: Parallel evolution and the extent to which it involves gene reuse have attracted much interest. Whereas it has theoretically been predicted under which circumstances gene reuse is expected, empirical studies that directly compare systems showing high and low parallelism are rare. Three‐spined stickleback ( Gasterosteus aculeatus ), where freshwater populations have been independently founded by ancestral marine populations, represent prime examples of phenotypic and genomic parallelism, but cases exist where parallelism is low. Based on RAD (restriction site associated DNA) sequencing, we analysed SNPs and chromosome inversions in populations in Denmark and Greenland showing low and high parallelism, respectively. We identified parallelism across freshwater populations in Greenland at genomic regions previously identified to be associated with marine–freshwater divergence. These same markers also separated Danish marine and freshwater sticklebacks, albeit to a weaker extent. Hence, parallelism was not absent in Denmark but possibly constrained by spatially and temporally varying selection. Divergence time estimates found one Danish freshwater population to be much older than the others. It also deviated strongly with respect to parallelism and may represent earlier postglacial colonization based on a different pool of standing variation and eliciting different adaptive responses to freshwater conditions. These findings provide empirical support to previous suggestions that the time since replicate populations had access to a common pool of standing variation is a major factor determining gene reuse. At last, based on the observed parallelism in the Greenlandic system we discuss the predictability of adaptive responses in newly established populations.